Peningkatan Hasil Belajar Siswa Dengan Model Discovery Learning Berbantuan Zoom Pada Mata Pelajaran Bahasa Indonesia Kelas V Sekolah Dasar - Mardiatama, Risa Arum (Universitas Sebelas Maret, 2020)
The learning outcomes of students of class V SDN Sumberagung 01 on the subjects of Bahasa Indonesia is still low. The cause is the activity of student learning is low and the use of learning model that is less varied. The purpose of this research is to improve student learning outcomes in subjects Bahasa Indonesia kelas V SDN Sumberagung 01 school year 2019/2020 through model Discovery learning assisted Zoom. The subject of research is the students of class V SDN Sumberagung 01, with the number of students as many as 10 children. The Data in this research is data about the improvement of learning outcomes of Indonesian Language through the use of model discovery learning assisted Zoom. The results showed that the application of the model the model of Discovery learning assisted Zoom can increase the mastery learning students. Learning outcomes students ranging from thepre-cycle to the second cycle in a row increased, i.e. 30%, 50%, and 90% with the average 59,00, 65.70, and 89,90.